OpenUNC: Collaborating to Increase the Visibility of Open Scholarship from the UNC System - Craft, Anna R. (Serials review, 2022)
This conference report covers a lightning talk from the 2022 North Carolina Serials Conference on the topic of OpenUNC, a collaborative website that shares information about and links to open access efforts and content from institutions in the University of North Carolina System. Site background, content, and opportunities for use are covered.